2022
DOI: 10.1128/spectrum.00290-22
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Culturable Phosphate-Solubilizing Bacteria in Soil Aggregates and Their Potential for Phosphorus Acquisition

Abstract: Phosphate-solubilizing bacteria are responsible for inorganic P solubilization and organic P mineralization. Elucidating the linkage between phosphate-solubilizing bacterial number and P-cycling-related gene abundance is important to isolate plant-growth-promoting bacteria for agro-ecosystems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…By contrast, other study observed isolated Pseudomonas sp. strain PSB-2 exhibited good solubilization of TCP with a high SI (>4.0) (He and Wan, 2022). In the present study, MQR6 T was isolated from the rhizosphere soil of A. truncatum, and showed clear halos of solubilizing TCP with the largest SI value of 3.98.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…By contrast, other study observed isolated Pseudomonas sp. strain PSB-2 exhibited good solubilization of TCP with a high SI (>4.0) (He and Wan, 2022). In the present study, MQR6 T was isolated from the rhizosphere soil of A. truncatum, and showed clear halos of solubilizing TCP with the largest SI value of 3.98.…”
Section: Discussionmentioning
confidence: 52%
“…Gluconic and 2-keto gluconic acids produced by bacteria play an important role in weathering and solubilization of phosphate in soil, acting as Ca 2+ chelators and providing the acidification of the external environment to dissolve the sparingly soluble calcium phosphates (Yu et al, 2011). Furthermore, the glucose dehydrogenase (gcd) gene, coding for the first enzyme in the direct oxidation pathway, contributes significantly to mineral phosphate solubilization by the plant growth-promoting rhizabacteria (Shariati et al, 2017;He and Wan, 2022). Similarly, our study revealed that the genes related to gluconic and 2-keto-Dgluconic acid production were found in the strain MQR6 T , including gcd, gdh, pqq, and bet (Table S3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results confirmed the hypothesis that gcd community was obviously affected by land reclamation, and it was closely associated with labile and moderately labile legacy P fractions. From the practical viewpoint, the inoculation of effective gcd ‐harboring species as an environment friendly alternative to conventional chemical P fertilization is a promising P management strategy (He & Wan, 2022; Islam & Hossain, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Soil carbon storage, nutrient availability, and biodiversity maintenance are strongly regulated by soil microorganisms, which convert soil nutrients, neutralize pollutants, and interact with each other [8][9][10]. The metabolites of soil microorganisms promote the dissolution of insoluble substances in soil; for example, phosphate-solubilizing bacteria can decompose P in phosphate ores, and potassium-solubilizing bacteria can decompose K in potassium ores to facilitate crop absorption and utilization [11,12]. Soil microorganisms are also involved in the decomposition and utilization of urea, and some fixate nitrogen by converting atmospheric N into fixed nitrides for plant use [13].…”
Section: Introductionmentioning
confidence: 99%